Gram-positive enhancer matrix delivering FVpE via M cell targeting elicit protective mucosal and adaptive immune responses against Helicobacter pylori infection - Zhang, Furui; He, Yaqin; Liu, Hongpeng; Wu, Jing; Li, Xin; Chen, Jiale; Ni, Linhan; Zhang, Zhen; Chen, Juan; Liu, Kunmei; Guo, Le (Frontiers in Immunology, 2025)
BackgroundThe Gram-positive enhancer matrix (GEM) is a novel mucosal vaccine delivery system based on lactic acid bacteria (LAB). Helicobacter pylori (H. pylori) mainly colonize the gastric mucosa and thus induce various gastric diseases. Hence, the development of an efficient mucosal vaccine is expected to be a new strategy for the prevention and treatment of H. pylori.Methods and ResultsThis study is based on the GEM delivery system, which constructs an oral vaccine targeting intestinal M cells, GEM-SAM-FVpE. Here, SAM represents the surface anchoring protein (cA) and the M cell-targeting peptide (Mtp), thereby enabling both efficient display on the GEM particle and targeted to intestinal M cells. And FVpE denotes the H. pylori multi-epitope antigen. As a results, GEM is able to successfully display the purified antigen SAM-FVpE on the surface, with a display efficiency of 90%. Meanwhile, GEM-SAM-FVpE enhances antigen presentation efficiency and activates DCs by upregulating MHC II and costimulatory molecules (CD80/CD86/CD40), and increasing the secretion of related cytokines. In vivo experiments indicate that oral administration of the GEM-SAM-FVpE significantly induces the production of high titers of sIgA, serum IgG, and its subtype, initiating mucosal and humoral immune responses, and inhibiting the adhesion of H. pylori to normal gastric mucosal epithelial cells. In addition, by significantly activating Th1, Th2, and Th17, it initiates antigen-specific cellular immune responses. Finally, H. pylori-infected mice treated with GEM-SAM-FVpE can significantly reduce the colonization of H. pylori in gastric tissue while also decreasing gastric mucosal damage.ConclusionGEM-SAM-FVpE can effectively induce protective mucosal responses and adaptive immune responses against H. pylori infection, providing a new scheme for the development of oral vaccines against H. pylori.